Advertisements
Advertisements
Question
If (secA + tanA)(secB + tanB)(secC + tanC) = (secA – tanA)(secB – tanB)(secC – tanC) prove that each of the side is equal to ±1. We have,
Sum
Solution
(secA + tanA)(secB + tanB)(secC + tanC) = (secA – tanA)(secB – tanB)(secC – tanC)
Multiplying both sides by
(secA – tanA)(secB – tanB)(secC – tanC) we get
(secA + tanA) (secB + tanB) (secC + tanC) (secA – tanA) (secB – tanB)
`(secC – tanC) = (secA – tanA)^2 (secB – tanB)^2 (secC – tanC)^2`
`(sec^2 A – tan^2 A)(sec^2 B – tan^2 B) (sec^2 C – tan^2 C) = (secA – tanA)2(secB – tanB)2(secC – tanC)^2`
`1 = [(secA – tanA)(secB – tanB) (secC – tanC)]^2`
(secA – tanA)(secB – tanB)(secC – tanC) = ±1
Similarly, multiplying both sides by
(secA + tanA)(secB + tanB)(secC + tanC),
we get
(secA + tanA)(secB + tanB)(secC + tanC) = ±1
shaalaa.com
Is there an error in this question or solution?